Beginning VB 2005 Databases From Novice to Professional - Huddleston, James; Raghuram, Ranga; Gilani, Syed Fahad; Pedersen, Jacob Hammer; Reid, Jon.; SpringerLink (Online service) (Berkeley, CA : Apress, 2007)
Beginning Visual Basic 2005 Databases teaches you everything you need to know about relational databases, SQL, and ADO.NET 2.0, giving you a sound start in developing console and Windows database applications. The book also includes chapters on the new SQL Server XML data type and the forthcoming LINQ enhancements to the next version of Visual Basic. In addition to teaching you database basics like using SQL to communicate with databases, this book provides you with detailed, code-practical techniques to access data in VB 2005 across a range of coding situations. Code-heavy and full of practical detail, this book has been fully revised and upgraded for .NET 2.0 and offers you the best contemporary practice in this core programming area, so that youll find yourself using it in nearly all your .NET projects.
Getting Our Tools -- Getting to Know Our Tools -- Introducing SQL -- Introducing ADO.NET -- Introducing Connections -- Introducing Commands -- Introducing Data Readers -- Introducing Datasets and Data Adapters -- Introducing Data Binding -- Understanding Tables and Relationships -- Learning More About Queries -- Using Stored Procedures -- Handling Exceptions -- Using Transactions -- Working with ADO.NET Events -- Working with Text and Binary Data -- Using XML -- Introducing LINQ.
Keywords: Computer science; Software engineering; Computer Science; Software Engineering/Programming and Operating Systems; Electronic books